Analysis of Phenolic Compounds by LC-HRMS and Determination of Antioxidant and Enzyme Inhibitory Properties of Verbascum speciousum Schrad - Kiziltas, Hatice; Bingol, Zeynebe; Goren, Ahmet C.; Alwasel, Saleh H.; Gulcin, Ilhami (Acg Publications, 2023)
Studies have shown an inverse correlation between age-related illnesses like coronary heart disease and cancer and fruit and vegetable intake. Given the probable health benefits of natural antioxidants from plants, research on them has increased. Verbascum L is a large genus of Scrophulariaceae family and 323 species distributed worldwide. Since Verbascum L. species are plants that are grown in many regions of Turkiye and are used in folk medicine, it is important to evaluate the biological activity of these species. In this study antioxidant properties of Verbascum speciosum Schrad. were investigated. The antioxidant capacities of water and ethanol-based extracts obtained from air parts were evaluated with Fe3+ reducing, CUPRAC, FRAP, DPPH center dot, and ABTS(center dot+) scavenging antioxidant methods. Extracts were also examined to determine their AChE, alpha-glycosidase and alpha-amylase enzyme inhibitions. This investigation could be a basis for further phytochemical investigations of Verbascum speciosum Schrad.
Keywords: Verbascum speciosum; antioxidant activity; reducing power; radical scavenging; enzyme inhibition